2021
DOI: 10.1007/s40618-021-01656-8
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid function in the subacute phase of traumatic brain injury: a potential predictor of post-traumatic neurological and functional outcomes

Abstract: Purpose That thyroid hormones exert pleiotropic effects and have a contributory role in triggering seizures in patients with traumatic brain injury (TBI) can be hypothesized. We aimed at investigating thyroid function tests as prognostic factors of the development of seizures and of functional outcome in TBI. Methods This retrospective study enrolled 243 adult patients with a diagnosis of mild-to-severe TBI, consecutively admitted to our rehabilitation uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 55 publications
(65 reference statements)
2
10
1
Order By: Relevance
“…What is surprising is that in the overall trend of laboratory findings of inflammation/coagulopathy/fibrinolysis in ESS patients at different time points, most parameters emerged a turning point at T3 (D9-D11 after admission), which is almost certainly a critical period related to prognosis. CRP, D-dimer, and fibrinogen (FIB) increased at the initial phase of SARS-COV-2 infection, with two peaks at day 5 and day 9 (30). CRP played an important role in inflammation, the tissue factor (TF) pathway, blood coagulation, endogenous fibrinolytic capacity, and the susceptibility of venous thromboembolism (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…What is surprising is that in the overall trend of laboratory findings of inflammation/coagulopathy/fibrinolysis in ESS patients at different time points, most parameters emerged a turning point at T3 (D9-D11 after admission), which is almost certainly a critical period related to prognosis. CRP, D-dimer, and fibrinogen (FIB) increased at the initial phase of SARS-COV-2 infection, with two peaks at day 5 and day 9 (30). CRP played an important role in inflammation, the tissue factor (TF) pathway, blood coagulation, endogenous fibrinolytic capacity, and the susceptibility of venous thromboembolism (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…In this pioneering study we found that, independently from confounders, lower baseline TSH levels and higher TSH increments during 6-months inpatient neurorehabilitation predicted an improvement of DoC, while baseline fT4 and fT3 levels and their variations during rehabilitation did not appear to play a role in DoC changes. Although serum TSH levels are usually normal during the post-acute phase of ABI, we were unable to find a correlation between TSH and THs, suggesting a central derangement of pituitary TSH secretion ( 33 ). It is known that thyrotropic axis signaling in the brain can be disrupted by a severe damage ( 34 ), likely through mechanisms that involved both THs signaling deregulation and alterations in TRH and TSH secretion and feedbacks ( 32 , 35 ).…”
Section: Discussionmentioning
confidence: 62%
“…The role of thyrotropic axis on rehabilitation and mortality after acquired brain injuries is still debated. In a previous study on patients with mild-to-severe TBI, we observed that increasing TSH and declining fT3 levels were associated with worst neurological and functional outcomes, as well as with a higher risk of mortality within 6 months following TBI ( 33 ). In this cohort, a narrower variation of fT4 levels was associated with an improvement in functional disability level and cognitive functions.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations